2022
DOI: 10.1097/nrl.0000000000000474
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ischemic Stroke Among Cannabis Users in the United States and Possible Risk Factors for Mortality

Abstract: Background: With changes in state laws, cannabis is now more accessible in many parts of the United States. The drug has previously been associated with a higher incidence of acute ischemic stroke (AIS). Our study analyzed the effect of cannabis use on AIS outcomes. Methods: The 2019 National Inpatient Sample from Healthcare Cost and Utilization Project and Agency for Healthcare Research and Quality was used to evaluate the AIS patients ages 25 and more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Tobacco smoking has also been linked with cannabis dependence [ 39 , 40 ]. While prior studies observed a lower obesity rate among cannabis users admitted for ischaemic stroke or myocardial infarction, our sample had a higher proportion of cannabis users classified as obese [ 30 , 41 , 42 ]. Importantly, even after propensity matching and adjusting for these potential confounders, cannabis use continued to be associated with a survival benefit in AMI.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Tobacco smoking has also been linked with cannabis dependence [ 39 , 40 ]. While prior studies observed a lower obesity rate among cannabis users admitted for ischaemic stroke or myocardial infarction, our sample had a higher proportion of cannabis users classified as obese [ 30 , 41 , 42 ]. Importantly, even after propensity matching and adjusting for these potential confounders, cannabis use continued to be associated with a survival benefit in AMI.…”
Section: Discussionmentioning
confidence: 69%
“…Our sample consisted of hospitalisations with a primary diagnosis of AMI via ICD-9 and ICD-10 codes from past studies. All cases that qualified as “Drug Abuse” based on ICD-9 and ICD-10 codes were excluded from our control group [ 30 ]. We studied the prevalence of multiple comorbidities as well as patient and hospital characteristics between cannabis users and non-users.…”
Section: Methodsmentioning
confidence: 99%
“…Since the ICD-10 code for prediabetes was introduced in 2016, and it did not cover all the months of that particular year, we focused on the 2017–2020 data for our prediabetes group. We also estimated the incidence of acute myocardial infarction (AMI) and acute ischemic stroke (AIS) over these 5 years [ 10 , 11 ]. Linear-by-linear analyses, as per past studies of the NIS, were used to estimate trends [ 12 ].…”
mentioning
confidence: 99%